Contactin-Associated Protein (Caspr) and Contactin Form a Complex That Is Targeted to the Paranodal Junctions during Myelination - Rios, Jose C. (J Neurosci, 2000)
Specialized paranodal junctions form between the axon and the closely apposed paranodal loops of myelinating glia. They are interposed between sodium channels at the nodes of Ranvier and potassium channels in the juxtaparanodal regions; their precise function and molecular composition have been elusive. We previously reported that Caspr (contactin-associated protein) is a major axonal constituent of these junctions (Einheber et al., 1997). We now report that contactin colocalizes and forms a cis complex with Caspr in the paranodes and juxtamesaxon. These proteins coextract and coprecipitate from neurons, myelinating cultures, and myelin preparations enriched in junctional markers; they fractionate on sucrose gradients as a high-molecular-weight complex, suggesting that other proteins may also be associated with this complex. Neurons express two contactin isoforms that differ in their extent of glycosylation: a lower-molecular-weight phosphatidylinositol phospholipase C (PI-PLC)-resistant form is associated specifically with Caspr in the paranodes, whereas a higher-molecular-weight form of contactin, not associated with Caspr, is present in central nodes of Ranvier. These results suggest that the targeting of contactin to different axonal domains may be determined, in part, via its association with Caspr. Treatment of myelinating cocultures of Schwann cells and neurons with RPTPβ–Fc, a soluble construct containing the carbonic anhydrase domain of the receptor protein tyrosine phosphatase β (RPTPβ), a potential glial receptor for contactin, blocks the localization of the Caspr/contactin complex to the paranodes. These results strongly suggest that a preformed complex of Caspr and contactin is targeted to the paranodal junctions via extracellular interactions with myelinating glia.